2013
DOI: 10.1089/cbr.2012.1404
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 96 and α-Fetoprotein Cross-Linking Complexes Elicited Specific Antitumor Immunity

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant gastroenterological cancers over the world. α-fetoprotein (AFP) is an oncofetal protein produced during HCC development that could generate weaker and less reproducible antitumor protection, and it may serve as a target for immunotherapy. Therefore, it is imperative to enhance its immunogenicity and develop therapeutic vaccines to eliminate AFP-expressing tumors. In this study, by way of glutaraldehyde cross-linking, we constructed a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Consistent with the findings further researches have also confirmed that conjugating HSP70 to AFP antigen could improve the potency of AFP fusion vaccines [ 49 , 50 , 63 68 ]. In recent years, we developed a series of potential therapeutic proteins or peptide vaccines HSP70-AFP, HSP70-AFP-P, and gp96-AFP-P; the recombinant vaccine can induce specific antitumor immunity against AFP-positive tumor cells [ 49 , 50 , 67 ]. Most of all, a novel therapeutic vaccine, HSP70-P/AFP-P, was constructed to enhance the immunogenicity of AFP by conjugating AFP epitope peptide with the HSP70 functional peptide via peptide synthesis.…”
Section: Application Of Afp In the Immunotherapy Of Hepatocellularmentioning
confidence: 99%
“…Consistent with the findings further researches have also confirmed that conjugating HSP70 to AFP antigen could improve the potency of AFP fusion vaccines [ 49 , 50 , 63 68 ]. In recent years, we developed a series of potential therapeutic proteins or peptide vaccines HSP70-AFP, HSP70-AFP-P, and gp96-AFP-P; the recombinant vaccine can induce specific antitumor immunity against AFP-positive tumor cells [ 49 , 50 , 67 ]. Most of all, a novel therapeutic vaccine, HSP70-P/AFP-P, was constructed to enhance the immunogenicity of AFP by conjugating AFP epitope peptide with the HSP70 functional peptide via peptide synthesis.…”
Section: Application Of Afp In the Immunotherapy Of Hepatocellularmentioning
confidence: 99%
“…A phase I clinical trial demonstrated that all six tested patients generated CD8-positive T-cell responses to the peptides as measured by direct IFN-γ enzyme-linked immunospot (ELIspot) and MHC class I tetramer assays[ 26 ]. Specific CD8-positive T cell response may be augmented by the use of AFP conjugated with heat shock protein (HSP)70[ 27 ], HSP72[ 27 ], or glycoprotein 96[ 28 ], as revealed by studies using mouse AFP-expressing tumors. Butterfield and colleagues further examined the efficacy of AFP-pulsed DC transfer and demonstrated that six out of the ten subjects generated significant AFP-positive T cell responses to the administered peptides, although nine showed progressive disease[ 26 ].…”
Section: Current and Emerging Immunotherapy Approachesmentioning
confidence: 99%
“…The vaccines acted synergistically to significantly increase the AFP‐specific CD8 + T cell responses and produced an impressive cytotoxic antitumor effect against AFP‐expressing tumors. These data suggested that tumor vaccines by cross‐linking tumor antigen and heat shock protein 72 and glycoprotein 96 are promising approaches to cancer therapy . Diethylnitrosamine injected into infant mice resulted in the development of multinodular HCC in which AFP is expressed.…”
Section: Immunotherapeutic Strategiesmentioning
confidence: 99%